2020
DOI: 10.1186/s12864-020-06800-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of an allotetraploid interspecific CSSLs guides interspecific genetics and breeding in cotton

Abstract: Background: The low genetic diversity of Upland cotton limits the potential for genetic improvement. Making full use of the genetic resources of Sea-island cotton will facilitate genetic improvement of widely cultivated Upland cotton varieties. The chromosome segments substitution lines (CSSLs) provide an ideal strategy for mapping quantitative trait loci (QTL) in interspecific hybridization. Results: In this study, a CSSL population was developed by PCR-based markers assisted selection (MAS), derived from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 58 publications
1
10
0
1
Order By: Relevance
“…Therefore, it was still valid to carry out the current QTL analysis in the BIL population developed from the two parents. The results further showed that the two parents of different species possessed different genetic loci involved in MIC formation in that both parents had QTL alleles decreasing MIC (8 QTLs in CRI36 vs. 17 QTLs in Hai7124), consistent with many previous QTL studies in cotton (Lacape et al, 2010;Zhang et al, 2014Zhang et al, , 2020Zhu et al, 2020). As such, transgressive segregation in MIC was observed in that the BILs developed from the two parents had MIC ranging from 2.10 to 6.17, with an average BLUP of 4.18.…”
Section: Populations From Parents With Low Fiber Micronaire Could Be Used For Quantitative Trait Locus Analysissupporting
confidence: 89%
“…Therefore, it was still valid to carry out the current QTL analysis in the BIL population developed from the two parents. The results further showed that the two parents of different species possessed different genetic loci involved in MIC formation in that both parents had QTL alleles decreasing MIC (8 QTLs in CRI36 vs. 17 QTLs in Hai7124), consistent with many previous QTL studies in cotton (Lacape et al, 2010;Zhang et al, 2014Zhang et al, , 2020Zhu et al, 2020). As such, transgressive segregation in MIC was observed in that the BILs developed from the two parents had MIC ranging from 2.10 to 6.17, with an average BLUP of 4.18.…”
Section: Populations From Parents With Low Fiber Micronaire Could Be Used For Quantitative Trait Locus Analysissupporting
confidence: 89%
“…Full utilization of genetic resources of G. barbadense with excellent fiber quality should be considered to promote genetic enhancement of widely cultivated G. hirsutum varieties (Zhu et al, 2020). Eight superior lines with the best comprehensive LP, FL, FS, and FM phenotypes in four environments were identified in the CSSLs population (Table 3).…”
Section: Excellent Introgression Lines With More Favorable Qtl Allele...mentioning
confidence: 99%
“…Chromosomes or genes introduced to G. hirsutum from G. barbadense and other tetraploid Gossypium species were found to affect cottonseed oil content substantially, based on CSLs ( Wu et al, 2009 , 2010 ; Bellaloui et al, 2020 ; Saha et al, 2020 ). Multiple QTL alleles from G. barbadense were demonstrated as highly promising for enhancing seed oil content in introgressed G. hirsutum lines ( Zhu et al, 2020 ). Therefore, introgression breeding between G. hirsutum and G. barbadense may greatly improve the content of seed oil content and possibly fatty acid composition.…”
Section: Quantitative Trait Loci Mapping and Genomewide Association S...mentioning
confidence: 99%